Estudo das toxicidades do extrato fluido de Solanum paniculatum L. - Jesus, Patricia Romualdo de (2020)
Solanum paniculatum L. is a medicinal plant belonging to the Solanaceae family, popularly known as “jurubeba verdadeira”. It is used by the community for the treatment of liver and gastric disorders, in addition to culinary use. Considering the shortage of studies on the use of jurubeba, this work aimed to evaluate the phytochemical profile and acute oral toxicity and repeated doses of 28 days of fluid extract from the leaves of Solanum paniculatum L. (FESP). The phytochemical composition was performed through analyzes by HPLC-ESI-MS/MS and GC/MS. The study of acute toxicity and repeated doses of 28 days followed the guidelines of OECD 423 and 407, respectively. In the acute toxicity study, a single dose of 2000 mg/kg of FESP was administered to Wistar rats and behavioral observations were made for 14 days. In the repeated dose toxicity study, FESP was administered at doses of 500, 750 and 1000 mg/kg over 28 days in male and female Wistar rats and behavioral changes, body weight and food consumption of the animals were observed. At the end of the experiment, blood samples were collected for biochemical and hematological analyzes. The liver, kidney and stomach organs were collected for histopathological analysis. In addition to these organs, heart and spleen were collected to analyze the relative weight of the organs. In the phytochemical profile, steroidal alkaloids, jurubine, isojuripidine and jurubidine were identified. In the acute administration of FESP there were no deaths or signs of toxicity. Thus, FESP can be classified in category 5 (OECD), in which it is considered safe at a dose of 2000 mg/kg. Repeated administration of FESP at doses of 500, 750, and 1000 mg/kg did not cause death or behavioral changes. Biochemical parameters showed a decrease in triglyceride levels in the groups of males and females treated at the dose of 1000 mg/kg when compared to the groups of males and females treated at the doses of 750 and 500 mg/kg. In histopathological analysis, hydropic degeneration was observed in male rats treated at the dose of 750 and 1000 mg/kg, in the group of females treated at the dose of 1000 mg/kg, sparse focal points of necrosis were observed. There was an increase in the relative liver weight of the males treated at a dose of 500, 750 and 1000 mg/kg compared to the control. These changes can be considered toxicity factors. Given this, the frequent use of jurubeba in the highest doses (750 and 1000 mg/kg) is not considered safe. However, more studies with different concentrations and periods are necessary to establish a safety parameter for the use of jurubeba.